The ETS-Domain Transcription Factor Elk-1 Regulates COX-2 Gene Expression and Inhibits Glucose-Stimulated Insulin Secretion in the Pancreatic β-Cell Line INS-1 - Xiong-Fei Zhang; Yi Zhu; Wen-Biao Liang; Jing-Jing Zhang (International Journal of Endocrinology)
Cyclooxygenase-2 (COX-2) expression is associated with many aspects of physiological and pathological conditions, including pancreatic β-cell dysfunction. Prostaglandin E2 (PGE2) production, as a consequence of COX-2 gene induction, has been reported to impair β-cell function. The molecular mechanisms involved in the regulation of COX-2 gene expression are not fully understood. We previously demonstrated that transcription factor Elk-1 significantly upregulated COX-2 gene promoter activity. In this report, we used pancreatic β-cell line (INS-1) to explore the relationships between Elk-1 and COX-2. We first investigated the effects of Elk-1 on COX-2 transcriptional regulation and expression in INS-1 cells. We thus undertook to study the binding of Elk-1 to its putative binding sites in the COX-2 promoter. We also analysed glucose-stimulated insulin secretion (GSIS) in INS-1 cells that overexpressed Elk-1. Our results demonstrate that Elk-1 efficiently upregulates COX-2 expression at least partly through directly binding to the −82/−69 region of COX-2 promoter. Overexpression of Elk-1 inhibits GSIS in INS-1 cells. These findings will be helpful for better understanding the transcriptional regulation of COX-2 in pancreatic β-cell. Moreover, Elk-1, the transcriptional regulator of COX-2 expression, will be a potential target for the prevention of β-cell dysfunction mediated by PGE2.